Optimizing Surveillance for South American Origin Influenza A Viruses Along the United States Gulf Coast Through Genomic Characterization of Isolates from Blue‐winged Teal (Anas discors). Issue 2 (24th July 2014) - Ramey, A. M.; Walther, P.; Link, P.; Poulson, R. L.; Wilcox, B. R.; Newsome, G.; Spackman, E.; Brown, J. D.; Stallknecht, D. E.
Summary: Relative to research focused on inter‐continental viral exchange between Eurasia and North America, less attention has been directed towards understanding the redistribution of influenza A viruses (IAVs) by wild birds between North America and South America. In this study, we genomically characterized 45 viruses isolated from blue‐winged teal ( Anas discors ) along the Texas and Louisiana Gulf Coast during March of 2012 and 2013, coincident with northward migration of this species from Neotropical wintering areas to breeding grounds in the United States and Canada. No evidence of South American lineage genes was detected in IAVs isolated from blue‐winged teal supporting restricted viral gene flow between the United States and southern South America. However, it is plausible that blue‐winged teal redistribute IAVs between North American breeding grounds and wintering areas throughout the Neotropics, including northern South America, and that viral gene flow is limited by geographical barriers further south (e.g. the Amazon Basin). Surveillance for the introduction of IAVs from Central America and northern South America into the United States may be further optimized through genomic characterization of viruses resulting from coordinated, concurrent sampling efforts targeting blue‐winged teal and sympatric species throughout the Neotropics and along the United States Gulf Coast.